(untitled) (Bangladesh Journal of Agricultural Research, 2009)
The genetics of salinity tolerance in rice was studied by visual scoring in parents F1 F2 and backcross generations of six crosses. Segregation analysis indicated partial dominance for salinity tolerance. Estimation of genetic parameters under epistatic model indicated the importance of additive effects in the inheritance of salinity tolerance. Highly significant additive type of gene action in Pokkali/BR29 and both additive and dominance type of gene action in Nonabokra/BR29 without interaction were observed suggesting absence of epistasis and validity of additive dominance model. Significant dominance effect of genes in Nonabokra/BR29 suggests the use of hybrid rice where production of hybrid rice seed is feasible. The non-interactions with duplicate type of epistasis were observed in the crosses with moderately tolerant and susceptible parents. As heritability of the trait was low to moderate, the breeding population must he large and selection for tolerance must be exercised in later generations under controlled conditions. Key words: Genetic analysis, salinity, rice. doi: 10.3329/bjar.v33i4.2284 Bangladesh J. Agril. Res. 33(4) : 519-529, December 2008